An Analysis on the Errors of The Tenth Grade Students Writing on the Descriptive Text - Wae Asae Wachi; Henri Fatkurochman; Yeni Mardiana Devanti (JELP Journal of English Language and Pedagogy, 2026)
This study aims to analyze the common errors made by tenth-grade students in writing descriptive texts and to identify the causes of these errors. Conducted at SMK Islam Bustanul Ulum Pakusari in the 2024/2025 academic year, the research employed a qualitative descriptive design. Data were collected through classroom observations, students’ written texts, and semi-structured interviews. The analysis reveals that students made various types of errors, including grammatical, lexical, spelling, and structural errors. The causes of these errors are categorized into three major factors: interlingual interference, intralingual interference, and carelessness. The findings indicate that students need more intensive writing practice and guidance in grammar and text structure. This study suggests that English teachers should design more structured and motivating writing exercises to reduce students’ writing difficulties.